Governance and transparency of the Chinese charity foundations. Issue 2 (7th May 2019) - Xue, Qingmei; Niu, Yuning
Abstract : Purpose: The purpose of this paper is to investigate the relation between various governance mechanisms and the transparency level by using a sample of the top 200 Chinese charity foundations on net assets. Design/methodology/approach: Three types of governance forces are examined, including the board, the management and the capital providers. The Foundation Transparency Index (FTI), published by Chinese Foundation Center, is used as a proxy for the transparency level. Findings: The evidences show that for the public foundations that can elicit fund from the public, providing compensation to the foundation managers could encourage them to increase the transparency level. Furthermore, the sophisticated donors also represent a useful governance force. For the non-public foundations that can only seek donors through private contacts, getting more members in their supervisory board and having more government grants are helpful in improving their transparency. The results are robust even after controlling for lagged FTI and other characteristics of foundations. And the transparency level is positively associated with the international connections for both types of foundations. Research limitations/implications: This research is based on a limited sample. The results can hardly generalize to the other smaller foundations. However, the results are still meaningful for to the legislators, regulators and managers of Chinese charity foundations. Because the result implies that the overseas donors are effective monitors that could improve the foundation transparency, the newly published law may weaken this governance force. Originality/value: This is the first paper that studies the governance of Chinese charity foundations. By using a third-party index to proxy for the transparency, the results complement existing literature.